Differences in Extended-Spectrum Beta-Lactamase Producing Escherichia coli Virulence Factor Genes in the Baltic Sea Region. (28th August 2014) - Lillo, Jana; Pai, Kristiine; Balode, Arta; Makarova, Mariia; Huik, Kristi; Kõljalg, Siiri; Ivanova, Marina; Kaftyreva, Lidia; Miciuleviciene, Jolanta; Naaber, Paul; Parv, Kristel; Pavelkovich, Anastasia; et al.
Abstract : The aim of this study was to compare the prevalence of different virulence factor (VF) genes in extended-spectrum beta-lactamase (ESBL) producing Escherichia coli strains isolated from the Baltic Sea region. A total of 432 strains of phenotypically ESBL positive E. coli were collected from 20 institutions located in Estonia, Latvia, Lithuania, and the region of St. Petersburg in Russia from January to May 2012 and analyzed for phylogenetic group and prevalence of 23 VF genes. The strains were collected from clinical material (urine, blood, wound, and respiratory tract). Bacterial isolates were compared according to phylogenetic group, clinical material, and geographical origin. Most of the VF genes were concentrated within phylogenetic group B2 and/or D. When comparing strains isolated from different countries, it was found that strains originating from Estonia and Latvia belonged mainly to group B2 and strains from Lithuania and Russia mainly to groups B2 and D. The P-fimbrial adhesin gene papEF was more prevalent in Russian strains, colicin gene cvaC in Lithuanian strains, and capsular gene kpsMTII in Latvian strains; serum resistant gene traT was less prevalent in Estonian strains. The regional differences of VF genes remained statistically significant after taking into account the phylogenetic distribution in the countries.